Regulation of bacteriocin production: the role of genes, quorum sensing, and environmental factors (the review) - Knysh, Oksans; Martynov, Artur (Annals of Mechnikov’s Institute, 2025)
The biosynthesis of bacteriocins requires high metabolic costs, so bacteria have developed regulatory mechanisms for their generation only upon necessity and in response to specific signals. Bacteriocin production is regulated by genetic factors, intricate quorum sensing (QS) systems and various environmental stimuli. The aim of this investigation was to evaluate the current knowledge about the mechanisms of regulation of bacteriocin production. Scope of review: The analysis included more than 30 studies, mostly from the last ten years. Conclusions: Currently, the mechanisms of genetic and quorum-sensing regulation of bacteriocin production have been largely elucidated. Factors influencing the ability of bacteria to produce bacteriocins were also identified. Among them, the most important are the media composition (carbon, nitrogen, vitamins, surfactants, etc.), cultivation conditions (temperature, pH, aeration, stirring, etc.), and co-cultivation. It has been experimentally proven that some microorganisms, when co-cultivated, are capable of inducing the production of bacteriocin by inactive bacteriocin-competent strains or enhancing the production of bacteriocin above the baseline level by a bacteriocinogenic strain. Development of co-culture-inducible bacteriocin-producing systems underlies one of the promising strategies for the creation of new effective antimicrobials for food preservation and antimicrobial therapy